2008
DOI: 10.1016/j.biopsych.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Shared Gene Expression Alterations in Schizophrenia and Bipolar Disorder

Abstract: Background-Schizophrenia and bipolar disorder together affect approximately 2.5% of the world population, and their etiologies are thought to involve multiple genetic variants and environmental influences. The analysis of gene expression patterns in brain may provide a characteristic signature for each disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(148 citation statements)
references
References 49 publications
6
141
1
Order By: Relevance
“…91,92 The results complement findings of transcriptomic investigations in these brain regions. 9,[93][94][95][96][97][98] In the cases of ANXA6, Bcl2 inhibitor protein BNIP3, N(G),N(G)-dimethylarginine dimethylaminohydrolase, galectin-1, and heat shock cognate 71-kDa protein, our findings are supported by recent genome-wide association studies. 99 Ingenuity Pathways Analysis in our study notably identified cellular assembly and organiza-ARCH GEN PSYCHIATRY/ VOL 68 (NO.…”
Section: Commentsupporting
confidence: 79%
“…91,92 The results complement findings of transcriptomic investigations in these brain regions. 9,[93][94][95][96][97][98] In the cases of ANXA6, Bcl2 inhibitor protein BNIP3, N(G),N(G)-dimethylarginine dimethylaminohydrolase, galectin-1, and heat shock cognate 71-kDa protein, our findings are supported by recent genome-wide association studies. 99 Ingenuity Pathways Analysis in our study notably identified cellular assembly and organiza-ARCH GEN PSYCHIATRY/ VOL 68 (NO.…”
Section: Commentsupporting
confidence: 79%
“…AGXT2L1 was reported to be among the most up-regulated brain-specific genes in bipolar disorder and schizophrenia (45). AGXT2L1 was down-regulated in suicide completers (46) and in 72% of major depressive disorder: suicide cases compared with agematched controls (47).…”
Section: Discussionmentioning
confidence: 93%
“…Some evidence suggests a role for GLT-1 in the pathophysiology of schizophrenia as follows: (1) a susceptibility locus for schizophrenia is probably located within or near the GLT-1 gene (Deng et al, 2004), and this gene is reportedly dysregulated in patients with schizophrenia (Shao and Vawter, 2008); (2) GLT-1 immunoreactivity is increased in the thalamus, striatum, and prefrontal cortex of schizophrenia patients McCullumsmith and Meador-Woodruff, 2002;Smith et al, 2001); (3) the antipsychotic clozapine specifically downregulates GLT-1 expression and function both in vivo and in vitro (Melone et al, 2001(Melone et al, , 2003VallejoIllarramendi et al, 2005); (4) the psychotomimetics PCP specifically upregulates GLT-1 expression and function (Fattorini et al, 2008); and (5) pharmacologically induced GLT-1 upregulation is associated with an impairment of the prepulse inhibition (PPI) of the startle reflex, a neurophysiological parameter altered in schizophrenia patients and in animal models of schizophrenia, in a dihydrokainate (DHK)-reversible manner, and worsens PCP-induced PPI alterations Melone et al, 2009b). These data support the hypothesis that, in concert with both NMDARs and non-NMDARs (Lewis and Gonzalez-Burgos, 2006; Lewis and Moghaddam, 2006), GLT-1 has a role in the dysfunction of glutamatergic transmission that contributes to the disturbance of information processing occurring in schizophrenia (Venables, 1960;McGhie and Chapman, 1961;Andreasen, 1997Andreasen, , 2000Tononi and Edelman, 2000).…”
Section: Introductionmentioning
confidence: 99%